Analisis Penentuan Harga Jual Produk dengan Menggunakan Metode Cost Plus Pricing dan Target Profit Pricing untuk Memaksimalkan Keuntungan - Oktaviana, Nita; Suyanto, Suyanto; Padwa Sari, Gustin (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze the calculation of production costs and determination of selling prices applied by the Metro Jaya Rambak Gurih Cracker Factory and compare them with the costplus pricing method and target profit pricing. The research method used is a quantitative approach with data collection through observation, interviews, and documentation. The results of the study indicate that the total production costs according to the company reached IDR 154,726,000, while the calculation using the full costing method reached IDR 155,162,454. These findings indicate that the target profit pricing method provides the highest profit potential, which is IDR 38,788,096, compared to other methods. From the results of the analysis, it is recommended that the Metro Jaya Gurih Rambak Crackers Factory implement a cost calculation and pricing method that is more in accordance with accounting standards, and use the target profit pricing method to maximize profits.